Role of epicardial adipose tissue volume as predictor of atrial fibrillation recurrence. (19th May 2022) - Fernandes, S; Cruz, I; Ladeiras-Lopes, R; Diaz, S; Silva, M; Barros, A; Saraiva, F; Faria, R; Almeida, J; Fonseca, P; Goncalves, H; Oliveira, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Several studies have demonstrated the relation between general obesity and atrial fibrillation (AF). Epicardial adipose tissue (EAT), due to its local paracrine effect and the intimate relation with the atrium, could influence AF recurrence rates, but very few studies have explored this association. Purpose: In this study we aimed to evaluate if EAT could be a predictor of AF recurrence after an AF ablation procedure. Methods: We included all consecutive patients submitted to AF ablation (2017-2019) who performed a computed tomography scan prior to the procedure. EAT volume was semi-automatically reconstructed by manually tracing the pericardium. Adipose tissue was defined in the range between -150 and -50 Hounsfield units. Recurrence was defined as any documented (ECG/Holter) episode of AF, atrial flutter or atrial tachycardia after 3 months of the procedure. Logistic regression with a restricted cubic polynomial transformation was used to model the non-linear relationship between recurrence and EAT volumes. Inspection of the partial effect curves suggested that a cutoff for EAT volume ≥80mL could stratify patients at risk of recurrence and a Time-to-event analysis was carried. Results: A total of 354 patients (66% male, median age 57 years [IQR 48–65] and 21% persistent AF) were included. During a median follow-up of 34 months [IQR 24-43], 117 patients (33%) had AF recurrence. These patients had a significantly greater EAT volume (76 mL [IQR 55-111] vs 72 mL [IQR 48-95], p=0.03) when compared to those without recurrence. Also, patients with higher EAT volume (≥ 80mL) had a higher risk of recurrence compared to patients with lower volume (Figure 1, log-rank test p=0.007). After adjusting for clinical risk factors (age, gender, hypertension, diabetes mellitus, obesity, thyroid disease, AF type and left atrial enlargement), higher EAT volume did not remain an independent predictor of AF recurrence (Figure 2, HR 1.25 [95% CI, 0.83-1.86] p=0.3). Conclusion: In this cohort of patients with AF submitted to catheter ablation, EAT volume ≥80mL was associated with increased risk of AF recurrence. However, it was not an independent predictor of AF recurrence after adjustment to clinical risk factors.